Creasy and Resnik's maternal-fetal medicine principles and practice - Creasy, Robert K.; Resnik, Robert; Greene, Michael F.; Iams, Jay D.; Lockwood, Charles J. (Elsevier/Saunders, 2014)
Features advances in basic science, clinical diagnosis, and management at your fingertips, equipping you with the evidence-based guidelines and knowledge that you need to ensure the best possible outcomes in maternal-fetal medicine.